Marketing resources, performance, and competitive advantage: a review and future research directions - Davcik, N.; Sharma, P. (Journal of Business Research, 2016)
Marketing scholars and practitioners recognize marketing resources as crucial drivers in the process by which firms develop their competitive advantages and achieve higher levels of performance. However, there is little agreement in the literature on what constitutes marketing resources or how these influence brand or firm performance. In this editorial article, the co-editors of this special issue identify and describe three distinct research streams related to marketing resources and performance, namely relation to firm/brand environment, marketing as an organizational function and marketing resource deployment. Next, they discuss the theoretical frameworks and contributions of the seminal research articles as well as the papers included in this special issue that represent these three themes. Finally, this editorial identifies some open questions and future research directions in this important research area.